2020
DOI: 10.1101/2020.06.10.144964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hijacking SARS-Cov-2/ACE2 receptor interaction by natural and semi-synthetic steroidal agents acting on functional pockets on receptor binding region

Abstract: The coronavirus disease 2019 (COVID-19) is a respiratory tract infection caused by the severe acute respiratory syndrome coronavirus (SARS)-CoV-2. In the light of the urgent need to identify novel approaches to be used in the emergency phase, a largely explored strategy has been the repurpose of clinically available drugs as new antivirals, by targeting different viral proteins. In this paper, we describe a drug repurposing strategy based on a virtual screening of druggable pockets located in the central -she… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Authors wish to thank all the donors for the kind collaboration. This manuscript has been released as a PrePrint (Carino et al, 2020).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Authors wish to thank all the donors for the kind collaboration. This manuscript has been released as a PrePrint (Carino et al, 2020).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Importantly, MRBs such as spironolactone possess a significant anti-androgenic activity, which may be beneficial in the context of SARS-CoV-2 infection, by inhibiting the androgen-dependent expression of “Transmembrane protease, serine 2” (TMPRSS2), a transmembrane protease crucial for SARS-CoV-2 entry ( Liaudet & Szabo, 2020 ). In addition, potassium canrenoate (the active metabolite of spironolactone) results in concentration (0.1-10 μM)-dependent reductions of the binding of the SARS-CoV-2 spike protein to the ACE2 receptor ( Carino et al, 2020 ). Increased plasma aldosterone levels associated with disease severity in COVID-19 patients ( Villard et al, 2020 ) suggest that MRBs may have beneficial effects in COVID-19.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
“…At clinically relevant concentrations, cortisone increases the replication of infectious bronchitis HCoV in tracheal organ cultures, whereas reproductive hormones, such as progesterone, estrogen, and testosterone, do not have this effect ( Ambali & Jones, 1990 ). In a recent in vitro study, steroids (glycyrrhetinic, oleanolic acid) and bile acid derivatives inhibited binding of the SARS-CoV-2 spike protein to ACE2 ( Carino et al, 2020 ). It was also reported that Ciclesonide, an inhaled corticosteroid, suppresses the replication of SARS-CoV-2 with an EC 90 of 0.55 μM in human bronchial epithelial cells ( Matsuyama et al, 2020 ).…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 99%
“…This binding is based on hydrophobic and polar interactions with the steroidal scaffold of glycyrrhetinic acid and further reinforced by many ion and hydrogen interactions. The ability of the most active compounds to prevent virus entry in the case of low viral load was further confirmed in an in vitro study [ 94 ].…”
Section: Food Compounds In Preliminary In Silico Studiesmentioning
confidence: 96%